ANALISIS KONTRIBUSI PAJAK KENDARAAN BERMOTOR RODA DUA DAN RODA EMPAT TERHADAP REALISASI PENERIMAAN PENDAPATAN ASLI DAERAH PADA UPT SAMSAT MEDAN SELATAN - MAJU SIREGAR (LP2MTBM MAKARIOZ, 2020)
The review to be achieved in this study is the first, to analyze the contribution of two-wheeled and four-wheeled motorvehicles to local revenue at the UPT SAMSAT in South Medan 2014-2017, second, to analyze the tax effectiveness of twowheeledand four-wheeled motor vehicles on regional original income at the UPT SAMSAT in South Medan 2014-2017. Thisstudy uses descriptive quantitative methods. Methods of collecting data through library research and documentation. Whilethe data analysis method used is contribution analysis and effectiveness analysis. Based on the results of the study, it canbe concluded that the tax contribution of two-wheeled and four-wheeled motor vehicles to the local revenue in the UPTSAMSAT in South Medan in 2014 - 2017 shows a very good category, with a percentage above 50%. In 2014 its contributionamounted to 80.10% and in 2015 its contribution was 81.51%, in 2016 its contribution was 81.36%, and in 2017 itscontribution was 83.11%. Likewise, the tax effectiveness of two-wheeled and four-wheeled motor vehicles on local revenuein the South Medan Samsat UPT shows fluctuations in 2014 with an effectiveness of 80.54%, in 2015 the effectiveness was92.31%, with the effective category, in 2016 its effectiveness was 80.41%, with the category quite effective, in 2017 itseffectiveness was 97.76%, with the effective category. The Faktor that hinder the service of motorized vehicle taxation in thesouthern field samsat are : means and prasarana, routine coordination, community participation, and the financial conditionofthe community.